STUDI LITERATUR TENTANG EFEKTIVITAS MEDIA PEMBELAJARAN AUGMENTED REALITY BERBASIS ANDROID PADA PEMBELAJARAN IPA DI SEKOLAH DASAR - Ida Puspita Sari; Ranti Anggraini Ranti Anggraini; Mirna Dewi; Syifa Salsabila Mahmudah (Program Studi Pendidikan Guru Sekolah Dasar-Universitas Muhammadiyah Kupang, 2023)
Natural science is a systematic science that can develop understanding and application of concepts to make a product. This article aims to examine the use of Android-based Augmented Reality in science subjects in elementary schools. Augmented reality is a technology that combines virtual objects with the real world. This technology can be used as an effective learning medium, especially in science subjects in elementary school. The method used is a literature review sourced from Google Scholar over a period of 5 years (2019-2023). The results of this research obtained data from the scholar.com database with the keywords using Android-based augmented reality in science subjects, totaling 1,150 articles and 6 articles that met the inclusion criteria for analysis. AR can make science learning more interesting and interactive. So, AR can help students understand difficult science concepts.